Peptide Amphiphile Nanofibers with Conjugated Polydiacetylene Backbones in Their Core - Hsu, Lorraine (2008)
The coupling of electronic and biological functionality through self-assembly is an interesting target in supramolecular chemistry. We report here on a set of diacetylene-derivatized peptide amphiphiles (PAs) that react to form conjugated polydiacetylene backbones following self-assembly into cylindrical nanofibers. The polymerization reaction yields highly conjugated backbones when the peptidic segment of the PAs has a linear, as opposed to a branched, architecture. Given the topotactic nature of the polymerization, these results suggest that a high degree of internal order exists in the supramolecular nanofibers formed by the linear PA. On the basis of microscopy, the formation of a polydiacetylene backbone to covalently connect the β-sheets that help form the fibers does not disrupt the fiber shape. Interestingly, we observe the appearance of a polydiacetylene (PDA) circular dichroism band at 547 nm in linear PA nanofibers suggesting the conjugated backbone in the core of the nanostructures is twisted. We believe this CD signal is due to chiral induction by the β-sheets, which are normally twisted in helical fashion. Heating and cooling shows simultaneous changes in β-sheet and conjugated backbone structure, indicating they are both correlated. At the same time, poor polymerization in nanofibers formed by branched PAs indicates that less internal order exists in these nanostructures and, as expected, then a circular dichroism signal is not observed for the conjugated backbone. The general variety of materials investigated here has the obvious potential to couple electronic properties and in vitro bioactivity. Furthermore, the polymerization of monomers in peptide amphiphile assemblies by a rigid conjugated backbone also leads to mechanical robustness and insolubility, two properties that may be important for the patterning of these materials at the cellular scale.